2 − n(n + 1)R = 0 6, Section 0.1: ρ2 ddρR2 + 2ρ dR dρ We look for the solutions in the form R = ρm . We get a characteristic equation m(m − 1) + 2m − n(n − 1) = 0. Using the formula for the roots of quadratic equation, solutions are m = n and m = −(n − 1). Since we assume, that n is an integer the solutions are different. Therefore, the general solution, is R = c1 ρn + c2 ρ−n+1 . 8, Section 0.1: (ex φ0 )0 + λ2 ex φ = 0 By the product rule, ex φ00 + ex φ0 + ex λ2 φ = 0 Factoring out ex , we get a second order linear differential equation with constant coefficients, φ00 + φ0 + λ2 φ = 0. We look for the solutions in the form φ = xµ . The characteristic equation: µ2 + µ + λ2 = 0. Solutions are µ1 = √ −1+ 1−4λ2 , 2 µ2 = √ −1− 1−4λ2 . 2 For −1/2 < λ < 1/2, the general solution is φ = c1 eµ1 x + c2 eµ2 x . For λ = ±1/2, the general solution is φ = c1 xe±1/2x + c2 e±1/2x . √ For λ > 1/2 √ or λ < −1/2, the general solution is φ = c1 e−1/2x cos( 1 − 4λ2 x/2)+ c2 e−1/2x sin( 1 − 4λ2 x/2) 16, Section 0.1: d2 u dt2 + 2a du + a2 u = 0, dt u1 = e−at Set u = u1 v. After we plug u in this form into the original equation, we get an equation v 00 = 0, so v = At + B So the general solution is u = Ate−at + Be−at 4, Section 0.2: d2 u + u = cos(wt), dt2 (w 6= 1) Then the general solution of the homogeneous equation u = c1 cos t + c2 sin t. 1)We assume w 6= −1. 1 d2 u dt2 + u = 0 is We find a particular solution of non-homogeneous equation by method of undetermined coefficients u1 = A cos(wt) + B sin(wt), u001 +u1 = −Aw2 cos(wt)−Bw2 sin(wt)+A cos(wt)+B sin(wt) = cos(wt) A= 1 , −w2 +1 B=0 So the general solution is u = c1 cos(t) + c2 sin(t) + 1 −w2 +1 cos(wt) 2)When w = −1, we need to look for particular solutions in the form u1 = At sin(t) + Bt cos(t). We find A = 1/2, B = 0 So the general solution is u = c1 sin(t) + c2 cos(t) + 1/2t sin(t) d r du = −1; u1 (r) = 1, u2 = ln(r) 18, Section 0.2: 1r dr dr First, we write the equation in the standard form d2 u 1 du + = −1 dr2 r dr The Wronskian is W (r) = 1/r Therefore, a particular solution is R r R −1 Rr dt + ln(r) 1 1/t dt = −r2 /4 + 1/2 ln(r) up = − 1 ln(t)(−1) 1/t 12, Section 0.3: First, we look for a particular solution in the form up = Ax2 + Bx + C, and we find A= w , 2P B = − wL , C = − wEI P 2P 2 So the general solution is q q P P u = c1 sin( EI x) + c2 cos( EI x) + u(0) = 0, so c2 = u(L) = 0, so c1 = wEI , 2P 2 √P − wEI 2 (1+cos( 2P sin( √P EI L) EI 2 L)) w 2 x 2P − wL x P − wEI 2P 2